Ultrasonic Studies of Molecular Interactions in Organic Binary Liquid Mixtures - S. Thirumaran; T. Alli; D. Priya; A. Selvi (E-Journal of Chemistry)
The ultrasonic velocity, density and viscosity have been measured for the mixtures of 1-alkanols such as 1-propanol and 1-butanol with N-N dimethylformamide (DMF) at 303 K. The experimental data have been used to calculate the acoustical parameters namely adiabatic compressibility (β), free length (Lf), free volume (Vf) and internal pressure (πi). The excess values of the above parameters are also evaluated and discussed in the light of molecular interaction existing in the mixtures. It is obvious that there is a formation of hydrogen bonding between DMF and 1-alkanols. Further, the addition of DMF causes dissociation of hydrogen bonded structure of 1-alkanols. The evaluated excess values confirm that the molecular association is more pronounced in system-II comparing to the system-I.